Investigating the effectiveness of using various mathematics learning media among students with various learning styles - Laswadi, Laswadi; Supriadi, Nanang; Khaidir, Christina; Anggoro, Bambang Sri (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Appropriate mathematics learning media is one factor determining the success of learning mathematics. Teachers can use various types of media to help students learn mathematics. However, teachers must consider the learning media's suitability with students' characteristics. This study aims to 1) reveal the most effective learning media for visual, auditory, and kinesthetic learning styles; 2) determine the interaction between learning media and learning styles on students' mathematics achievement. Therefore, this study used a 3 × 3 factorial design. The sample in this study was 29 eighth-grade students in junior high school. Researchers used questionnaires and mathematics achievement tests to collect research data to be analyzed quantitatively. The results show that interactive applications are the most effective learning media for students with different learning styles. Besides, there is a significant interaction effect between learning media and learning styles on students' mathematics achievement.